2018
DOI: 10.1002/2016tc004442
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Structural Evolution of a Continental Margin During Obduction Orogeny: Insights From the Jebel Akhdar Dome, Oman Mountains

Abstract: The structural evolution of the carbonate platform in the footwall of the Semail ophiolite emplaced onto the passive continental margin of Arabia helps to better understand the early stages of obduction‐related orogens. These early stages are rarely observable in other orogens as they are mostly overprinted by later mountain building phases. We present an extensive structural analysis of the Jebel Akhdar anticline, the largest tectonic window of the Oman Mountains, and integrate it on different scales. Outcrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 104 publications
(186 reference statements)
3
61
0
Order By: Relevance
“…This depth is not only controlled by mechanical stratigraphy resulting from interlayering of lava flows and ash and scoria layers; lava flows themselves have different strengths depending on their degree of fracturing and jointing. Furthermore, the occurrence of open fractures at depth depends on fluid pressure (Townend and Zoback, 2000); in cohesive carbonates dilatant open fractures have been observed at depths of several kilometers, associated with high fluid pressures (Hilgers et al, 2006;Grobe et al, 2018). We are not aware of fluid pressure data from Iceland measured at depths >1 km and consequently as of now the depth below which open fractures can be maintained remains speculative.…”
Section: Oblique Faults On Icelandmentioning
confidence: 96%
“…This depth is not only controlled by mechanical stratigraphy resulting from interlayering of lava flows and ash and scoria layers; lava flows themselves have different strengths depending on their degree of fracturing and jointing. Furthermore, the occurrence of open fractures at depth depends on fluid pressure (Townend and Zoback, 2000); in cohesive carbonates dilatant open fractures have been observed at depths of several kilometers, associated with high fluid pressures (Hilgers et al, 2006;Grobe et al, 2018). We are not aware of fluid pressure data from Iceland measured at depths >1 km and consequently as of now the depth below which open fractures can be maintained remains speculative.…”
Section: Oblique Faults On Icelandmentioning
confidence: 96%
“…The highlighted differences in the tectonic evolution of Central Oman Mountains and Musandam are likely indicative of noncylindrical structures for the Oman Mountains. Another evidence of noncylindrical structures is provided by minor differences in the tectonic evolution of the three tectonic windows of the Central and Southeastern Oman Mountains (Hawasina, Jabal Akhdar, and Saih Hatat), highlighted by Grobe et al (2018).…”
Section: Discussionmentioning
confidence: 98%
“…Owing to a lack of geochronological data, an earlier beginning of Cenozoic compression in the Musandam area cannot be excluded, as tentatively indicated by the dashed thrust in Figure 10c. This tectonic event may be interpreted as a result of the onset of collision between the Arabian and Eurasian plates (Figure 10c; e.g., Glennie et al, 1990; Grobe et al, 2018; Loosveld et al, 1996; Searle, 1988b; Searle et al, 2014). Underthrusting of Arabia beneath Eurasia began at least 35 Ma ago (Figure 10c; Bigi et al, 2018; Mouthereau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The final doming of the JAD occurred from Eocene to Miocene (Hansman et al, 2017(Hansman et al, , 2018Grobe et al, 2018Grobe et al, , 2019. This process was accompanied by extensional shearing at the northern and eastern margin of the dome (Mattern and Scharf, 2018;Scharf et al, 2019), and tilting of the Arabian rocks along a WNW-ENE trending rotation axis at the northern and southern margin of the dome by ∼30° and ∼20°, respectively (compare Beurrier et al, 1986;Rabu et al, 1986).…”
Section: Shd's Neoproterozoic Formations Differ From Jad's Includingmentioning
confidence: 98%
“…Obduction was followed by extension (e.g., Fournier et al, 2006;Searle, 2007;Mattern and Scharf, 2018;Grobe et al, 2018Grobe et al, , 2019 as indicated by extensional faults, which displaced the ophiolite Searle, 2007). It is worth mentioning that both SHD and JAD display large-scale listric normal faults bounding their flanks (Searle, 2007).…”
Section: Shd's Neoproterozoic Formations Differ From Jad's Includingmentioning
confidence: 99%